Internal Control Systems Implementation and Fraud Mitigation Nexus among Deposit Taking Saccos in Kenya - Wanjala, Kevin; Riitho, David Gathanju (Finance & Economics Review, 2020)
Purpose: This paper analyses the relationship between the implementation of internal control and fraud mitigation among the savings and credit cooperatives societies (Saccos) in Kenya. Methodology: To achieve the objective, specific variables were formulated based on the five components of internal control model. Particularly, the research focuses on the effect of control environment, control activities, monitoring, information and communication, and risk assessment, on fraud mitigation. Data was collected through the use of a structured questionnaire. Ordinary Least Square Regression approach was used for analysis. Results: The data analysis found that all the mentioned variables significantly affect fraud mitigation among Saccos in Kenya. Implications: The analysis highlighted that there is a need for Saccos to strive and implement internal control systems to a higher extent to cure the persistent problem of fraud that they grapple with. The analysis also recommends that Saccos should institute proper mechanisms to provide adequate checks during staff recruitment, install adequate security, provide regulation of valuable information access, they should also conduct regular monitoring of third party links with personnel as measures to mitigate fraud.